Connecting landscape conservation and management with traditional ecological knowledge: does it matter how people perceive landscape and nature - Carvalho, Ana Maria (2011)
Ethnobotanical surveys conducted in Trás-os-Montes (Portugal) highlighted a renewed interest in cultural values of landscapes. Long term interactions between traditional ecological knowledge (TEK) and natural processes provided landscapes characterized by high diversity and relative stability. Rural contexts are facing social and economical constraints and landscapes are change accordingly. On a basis of ethnographic methodologies (consented interviews and participant observation), recent landscape changes at a local level and people’ perceptions are briefly described and discussed as important tools for landscape conservation and management. Young and some middle aged people value some of these changes, which they consider less hard-working and a symbol of modernity. Others see actual transformations as a waste of resources and abandonment and thus landscape is perceived as unproductive, which is considered reprehensible. Most of the informants are aware of a dynamic process taking place and conscious that landscape, like themselves, must adapt to changing times.